2013
DOI: 10.1523/jneurosci.3980-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin-Induced Chemotaxis of Human Gliomas Requires the Activation of KCa3.1 and ClC-3

Abstract: Previous reports demonstrate that cell migration in the nervous system is associated with stereotypic changes in intracellular calcium concentration ([Ca2+]i), yet the target of these changes are largely unknown. We examined chemotactic migration/invasion of human gliomas to study how [Ca2+]i regulates cellular movement and to identify downstream targets. Gliomas are primary brain cancers which spread exclusively within the brain, frequently migrating along blood vessels to which they are chemotactically attra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(115 citation statements)
references
References 42 publications
4
111
0
Order By: Relevance
“…The KCa family of Ca 2 + -activated K + channels, especially KCa3.1, is overexpressed in 32% of the glioma patients, and its expression correlates with patient survival (126). KCa3.1 is localized at the leading edge of migrating cells, and its inhibition results in reduced migration (127,128). The bradykinin receptor B 2 (B 2 R) is also expressed at the leading edge of migrating glioma cells.…”
Section: Hydrodynamic Model Of Glioma Cell Migrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The KCa family of Ca 2 + -activated K + channels, especially KCa3.1, is overexpressed in 32% of the glioma patients, and its expression correlates with patient survival (126). KCa3.1 is localized at the leading edge of migrating cells, and its inhibition results in reduced migration (127,128). The bradykinin receptor B 2 (B 2 R) is also expressed at the leading edge of migrating glioma cells.…”
Section: Hydrodynamic Model Of Glioma Cell Migrationmentioning
confidence: 99%
“…The bradykinin receptor B 2 (B 2 R) is also expressed at the leading edge of migrating glioma cells. It is a critical attractor of glioma cells toward the vasculature, and an activator of ion channels (127,129). Binding of bradykinin to B 2 R leads to increases in intracellular Ca 2 + which induces the opening of the KCa3.1 and ClC-3 channels, resulting in the efflux of Cl − , K + , and water (16,127,130).…”
Section: Hydrodynamic Model Of Glioma Cell Migrationmentioning
confidence: 99%
“…This has been explained on the bases of BK activates K + efflux through KCa2+ involving both BKCa and SKCa (Liu, Freyer, & Hall, 2007), and such activation are suppressed by TEA preincubation. Recently, (Cuddapah, Turner, Seifert, & Sontheimer, 2013) demonstrated that KCa2+ channels are activated as a result of BK-dependent Ca 2+ increase.The main reason behind the vasoconstriction effect of TEA is that the muscle is under depolarization and Ca +2 enter the cells while BKCa +2 channel opens during hyperpolarization and cause relaxation (Sanchez & López-Zapata, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…[38,39]. Pharmacological inhibition or genetic knockdown of KCa3.1 disrupts chemotaxis towards either of these ligands [38,39].…”
Section: (A) Potassium Channelsmentioning
confidence: 99%
“…[38,39]. Pharmacological inhibition or genetic knockdown of KCa3.1 disrupts chemotaxis towards either of these ligands [38,39]. KCa3.1 is also required for the migration of neuroblasts, one of the purported brain tumour precursor cells, along the RMS [40].…”
Section: (A) Potassium Channelsmentioning
confidence: 99%